Innate immune defences in the human endometrium - King, Anne E (BioMed Central, 2003)
The human endometrium is an important site of innate immune defence, giving protection against uterine infection. Such protection is critical to successful implantation and pregnancy. Infection is a major cause of preterm birth and can also cause infertility and ectopic pregnancy. Natural anti-microbial peptides are key mediators of the innate immune system. These peptides, between them, have anti-bacterial, anti-fungal and anti-viral activity and are expressed at epithelial surfaces throughout the female genital tract. Two families of natural anti-microbials, the defensins and the whey acidic protein (WAP) motif proteins, appear to be prominent in endometrium. The human endometrial epithelium expresses beta-defensins 1–4 and the WAP motif protein, secretory leukocyte protease inhibitor. Each beta-defensin has a different expression profile in relation to the stage of the menstrual cycle, providing potential protection throughout the cycle. Secretory leukocyte protease inhibitor is expressed during the secretory phase of the cycle and has a range of possible roles including anti-protease and anti-microbial activity as well as having effects on epithelial cell growth. The leukocyte populations in the endometrium are also a source of anti-microbial production. Neutrophils are a particularly rich source of alpha-defensins, lactoferrin, lysozyme and the WAP motif protein, elafin. The presence of neutrophils during menstruation will enhance anti-microbial protection at a time when the epithelial barrier is disrupted. Several other anti-microbials including the natural killer cell product, granulysin, are likely to have a role in endometrium. The sequential production of natural anti-microbial peptides by the endometrium throughout the menstrual cycle and at other sites in the female genital tract will offer protection from many pathogens, including those that are sexually transmitted.